Transcription factor E2F7 activates PKMYT1 to partially suppress adriamycin sensitivity in gastric cancer through the MAPK signaling pathway - Xianjin Yang; Jie Zeng; Changhong Jiang; Yi Zhang; Xu Zhang (Permanyer, 2024)
Background: Adriamycin resistance remains an obstacle to gastric cancer chemotherapy treatment. Objective: The objective of this study was to study the role and mechanism of transcription factor E2F7 in sensitivity to ADM chemotherapeutic agents in gastric cancer. Methods: Cell viability and cell sensitivity were assessed by CCK-8 and IC50 values of ADM were calculated. The impact of ADM on cellular proliferative capacity was assessed through colony formation assay. The binding relationship between E2F7 and PKMYT1 was then verified by dual luciferase assay and chromatin immunoprecipitation assay. ERK1/ERK2 and p-ERK1/p-ERK2 protein expression levels were detected by western blot. Results: In both gastric cancer tissue and ADM-resistant cells, a conspicuous upregulation of E2F7 and PKMYT1 was observed. Upregulated PKMYT1 was notably enriched in the MAPK signaling pathway. Enhanced levels of E2F7 were shown to not only drive gastric cancer cell proliferation but also engender a reduction in the sensitivity of these cells to ADM. Furthermore, PKMYT1 emerged as a downstream target of E2F7. Activation of E2F7 culminated in the transcriptional upregulation of PKMYT1, and silencing E2F7 reversed the inhibitory impact of PKMYT1 overexpression on ADM sensitivity in gastric cancer cells. Conclusion: E2F7/PKMYT1 axis might promote the proliferation and partially inhibit ADM sensitivity of gastric cancer cells by activating the MAPK pathway.